2002
DOI: 10.1111/j.1574-6941.2002.tb00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative involvement of nitrate and nitrite reduction in the competitiveness of Pseudomonas fluorescens in the rhizosphere of maize under non-limiting nitrate conditions

Abstract: Competition between different isogenic mutants of Pseudomonas fluorescens unable to carry out the first steps of the denitrification pathway was compared in soil micro-columns non-planted or planted with maize. A new isogenic mutant of P. fluorescens YT101 affected in both nitrate and nitrite respirations was constructed and used as a model of non-denitrifying strain (FM69MS strain). The outcome of the selection exerted by the plant after co-inoculation of FM69MS at the same ratio either with an isogenic denit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…[26,27] and Azospirillum brasilense [28], are able to use nitrogen oxides as alternative electrons acceptors under oxygen limiting conditions, a process called denitrification. Denitrification has been shown to play a role in rhizosphere colonization, since mutants of P. fluorescens impaired in nitrate or nitrite reductases are deficient in the colonization of the rhizosphere [26,29,30]. Furthermore, it has been shown that denitrification is statistically associated with rhizosphere competence in rhizosphere isolated fluorescent pseudomonads [31].…”
Section: Resultsmentioning
confidence: 99%
“…[26,27] and Azospirillum brasilense [28], are able to use nitrogen oxides as alternative electrons acceptors under oxygen limiting conditions, a process called denitrification. Denitrification has been shown to play a role in rhizosphere colonization, since mutants of P. fluorescens impaired in nitrate or nitrite reductases are deficient in the colonization of the rhizosphere [26,29,30]. Furthermore, it has been shown that denitrification is statistically associated with rhizosphere competence in rhizosphere isolated fluorescent pseudomonads [31].…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the production of anti-microbial compounds and inhibition of growth within the endosphere can contribute to pathogen resistance (Mazzola et al, 2014 ; De Coninck et al, 2015 ) or biocontrol of the community (Vetsigian et al, 2011 ; Tyc et al, 2015 ), both mechanisms ultimately benefiting the host plant. Four endosphere isolates were capable of denitrification, which has been shown to be a beneficial function for competitive ability for P. fluorescens in the rhizosphere (Ghiglione et al, 2002 ) and for colonization in the endosphere in Ralstonia infections of plants (Dalsing et al, 2015 ), likely due to the growth advantage in micro-aerobic environments in the endosphere due to the ability to use nitrate as an electron acceptor.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, nir or nor mutants of Nitrosomonas european presented limited growth under denitrification conditions (Schmidt et al, 2004), whereas nir and nor mutants of Parococcus denitrificans and Rhodobacter sphaeroides are unable to grow (De Boer et al, 1996;Bartnikas et al, 1997). Moreover, competition assays performed by Philippot et al (1995) and Ghiglione et al (2000Ghiglione et al ( , 2002 between wild type and nir or nar mutants of P. fluorescens YT101 on maize roots demonstrated that nirS and narG genes confer to the P. fluorescens YT101 strain a competitive advantage in rhizosphere colonization. In addition, Mirleau et al (2001) demonstrated the role of nitrate reductase in the fitness of P. fluorescens C7R12 strain during in vitro and in planta assays (Mirleau et al, 2001).…”
Section: Ecological and Environmental Significance Of Anaerobic Respimentioning
confidence: 99%